Changing tracks: how different visual presentations of travel itineraries impact the choice between plane and train - Catarci, Daniele; Laasner Vogt, Lea; Reijnen, Ester (Frontiers in Psychology, 2025)
Despite the negative impact flying has on the environment, people too often seem to choose the plane over the train because it supposedly “saves them time.” However, these perceived time savings are often overestimated, and in reality, can be significantly smaller because people have (deliberately or not) forgotten to consider the time costs incurred at the airport for security checks or baggage collection, for example. We therefore wondered whether this illusion of time savings could be prevented or reduced by visually highlighting the total travel time, thereby increasing the choice of train. In our first randomized online study (N = 614) on work-related travel scenarios, we were indeed able to show that presenting a comprehensive itinerary (visualizing the total travel time) instead of just the flight time (standard itinerary) increased train choice from 66 to 79%. A second study (N = 383) confirmed the robustness of this effect across different travel distances and price scenarios. Although our intervention worked, it may prove challenging to implement. A third study (N = 198) therefore examined an alternative intervention, a company guideline discouraging plane travel, by emphasizing both the environmental impact and the limited net time savings. The results showed a comparable increase in train choice. Overall, these results show that drawing attention to overlooked but critical attributes of decision-making, such as the actual total travel time, can serve as a powerful nudge for more sustainable travel choices.